The Application of Discriminant Analysis to the Identification of Key Factors of the Development of Polish Cities - Batóg, Barbara; Batóg, Jacek (Acta Universitatis Lodziensis. Folia Oeconomica, 2019)
Due to limited resources, effective urban development policies require the identification of key development areas and priorities. The existing development strategies or results of statistical analyses can be used for this purpose. In the latter case, one of methods of multidimensional analysis can be used – discriminant analysis. Although it is applied to many areas on a microeconomic scale, e.g. in predicting the bankruptcy of enterprises, it was rarely used to assess the competitive position or the dynamics of development of cities. The main aim of the paper is to identify the most important factors of development of Polish cities with powiat status and to analyse changes of these factors in time. Apart from typical areas, such as investment, income, employment, debt, or migration, the analysis uses qualitative variables which allow us to assess whether the size of the city and its location determine the dynamics of city development. The authors have found that the key factors determining the development of the largest Polish cities are related to the situation on the labour market and investments incurred by companies as well as by the cities themselves.